Anterior Chamber Depth Changes after Uneventful Phacoemulsification - Tanveer Anjum Chaudhry, Mustafa Kamal Junejo (Pakistan Journal of Ophthalmology, 2016)
Purpose: To measure changes in anterior chamber depth (ACD) after uneventful cataract surgery through phacoemulsification along with intraocular lens (IOL) implantation in healthy eyes using ultrasonography (Amplitude Scan). Study Design: Prospective observational clinical case series. Place and duration of Study: Section of Ophthalmology, department of surgery, Aga Khan University Hospital Karachi Pakistan from September 2011 to March, 2012. Material and Methods: Seventy Four eyes (74 patients) underwent Ultrasonography A Scan to evaluate anterior chamber configuration before, 1 day after, 1 week after and 1 month post-operative. We measured central ACD. Pre-operative and post-operative data was compared by using paired t tests. Results: A total of 74 subjects were enrolled in this study. There were 42 males (56.8%) and 32 females (43.2%).Before surgery, overall mean anterior chamberdepth (mm) ACD was 3.02 ± 0.43; in males was 3.07 ± 0.43 and in females was 2.96 ± 0.43. Overall, the mean ACD after 1 day of cataract surgery 3.46 ± 0.44,after 1 week of surgery was 3.64 ± 0.46, and after 1 month of surgery was 3.81 ± 0.46.Significant increase of 0.73 ± 0.58mm (p < 0.0001) in the mean ACD was seen after 1 month of surgery. However , mean difference in ACD after 1 month of surgery between male and female groups was 0.11 ± 0.09; which was not statistically significant (p = 0.42). After uneventful phacoemulsification along with IOL implantation, the anterior chamber angle depth increased markedly. Conclusion: Following uneventful phacoemulsification along with Intraocular lens implantation, the ACD markedly increased which, was statistically significant. Ultrasound A Scan is simple and easily available tool for obtaining quantitative data about anterior chamber depth. Keywords: Cataract, Anterior Chamber Depth, Phacoemulsification, Ultrasonography A Scan.